2011
DOI: 10.1063/1.3650700
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Folding of glycosylated proteins under confinement

Abstract: Conjugating flexible polymers (such as oligosaccharides) to proteins or confining a protein in a restricted volume often increases protein thermal stability. In this communication, we investigate the interplay between conjugation and confinement which is not trivial as the magnitude and the mechanism of stabilization are different in each instance. Using coarse-grained computational approach the folding biophysics is studied when the protein is placed in a sphere of variable radius and is conjugated to 0–6 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…We observed that while order-promoting residues are equivalently distributed between N-linked glycosites and control ordered regions, the former are relatively further depleted of disorder-promoting residues compared to the latter. N-glycans have been shown through mounting theoretical 26,50 and experimental 51 evidence to impact the folding and structure of glycoproteins (although the relationship is not always positively regulatory) 52,53 . The triose core of N-glycoproteins enhances both the kinetics and stability of tertiary glycoprotein folds 54 .…”
Section: Discussionmentioning
confidence: 99%
“…We observed that while order-promoting residues are equivalently distributed between N-linked glycosites and control ordered regions, the former are relatively further depleted of disorder-promoting residues compared to the latter. N-glycans have been shown through mounting theoretical 26,50 and experimental 51 evidence to impact the folding and structure of glycoproteins (although the relationship is not always positively regulatory) 52,53 . The triose core of N-glycoproteins enhances both the kinetics and stability of tertiary glycoprotein folds 54 .…”
Section: Discussionmentioning
confidence: 99%
“…These effects demonstrate that glycosylation affects the protein energy landscape, and it has been suggested that protein stabilization by glycosylation may be due to an enthalpic effect resulting from interactions between the protein and the attached glycans (17,20,21). In silico studies using coarsegrained strategies corroborate the enthalpic stabilization of the Src-SH3 domain by different degrees of glycosylation (22). In contrast, other studies suggest that the stabilization might be due either to a "chaperone-like" activity of glycans (14,17) or to hydrophobic collapse resulting from impaired solvation of the protein (23) and is largely entropic in origin (14,17).…”
mentioning
confidence: 49%
“…These results suggest that the covalent immobilization of BOD in GO produced a reduction in protein dynamics by virtue of the covalent bond, while the adsorbed protein had a more dynamical structure. The confinement produced by GO can also modulate the biophysical and structural features of proteins [ 44 ]. This confinement can also be found inside the cell, where chaperonins produce a “cage effect” to facilitating protein folding, thereby helping them to reach their functional conformation [ 45 ].…”
Section: Resultsmentioning
confidence: 99%